Analysis Of The Influence Of Member's Commitment And Satisfaction On Loyalty Of Cooperative Members - I Gede Aryana Mahayasa; N M. Putri Martayanti (Warmadewa Management and Business Journal (WMBJ), 2020)
Members´ loyalty is a very important thing in the business of cooperatives, for the development and progress of cooperatives in the future. High members´ commitment and satisfaction in cooperatives greatly influence the attitude of members to use the products and services offered by cooperatives to make members more loyal. The study aims to determine the effect of a members´ commitment and satisfaction on the members´ loyalty. The population of this study was members of the KSP Dharma Dhita cooperative in Sanur, which numbered 172 people. The number of samples taken was 120 members. Data collectors are carried out through interviews, observation, literature, and questionnaires. The data analysis technique used is multiple linear regression. The research findings state that partially members´ commitment and satisfaction have a positive and significant effect on the members´ loyalty of KSP Dharma Dhita cooperative in Sanur. Simultaneously members´ commitment and satisfaction have a significant positive effect on the members´ loyalty of KSP Dharma Dhita in Sanur. To increase member's loyalty, members need to be aware of themselves to have high commitment and satisfaction for cooperatives to create prosperity for cooperatives, cooperative members and society in general.